PRIMARY MANAGEMENT EVALUATION OF SPINAL CASES BY PHYSICIANS IN SãO PAULO HEALTH NETWORKS - GABRIELA NEVES VAZ; FÁBIO ANTÔNIO VIEIRA; RENATO HIROSHI SALVIONI UETA; EDUARDO BARROS PUERTAS (Coluna/Columna)
ABSTRACT Objectives: To evaluate the clinical management of spinal pathologies by non-specialist medical professionals in the healthcare networks of the state of São Paulo. Methods: This descriptive cross-sectional observational study was conducted through self-administered online questionnaires. Results: Forty-five responses were obtained, 82% being family and community physicians and 52% having less than five years of graduation. Of the respondents, 91.5% felt capable of initially managing spine cases, and 62.2% reported occasionally referring cases. Only 52.2% worked in institutions that had a referral protocol for specialized care. There was no difference between the analyzed groups regarding the time of training. Conclusion: Healthcare professionals still lack sufficient resources to assist decision-making, and excessive referrals to specialized care still occur. To mitigate these problems, it is essential for healthcare professionals to have access to updated clinical guidelines and appropriate screening tools to assist in referral decision-making. Level of Evidence III; Retrospective Comparative Study.